Optimum hydraulic and structural design of multi-cell box culvert - Mohammed Aminu Aminu, . (2021)
The economical design of culvert is a vital engineering decision due to the multiple repetitive requirements in the construction of highway facility. It is therefore important to seek for the cost effective design technique in order to reduce the project cost of highways with high demand of such structures. The economic design can be achieved through conventional culvert design practice, but the maximum economy can only be achieved by optimizing the design. The optimization procedure shall be applied from the hydrologic design, via the hydraulic design to the structural design in order to yield hydrological, hydraulic, and structurally optimal designed culvert structure. The hydraulic design determined the size of the culvert and barrel number requirement for the structure to control the passage of storm water flow through it, with risk, economy, property damage, highway overtopping and damage, in mind. Effective structural design is necessary for the resistance of the structure to various load combination induced from the highway traffic, overfill material, backfill material, hydrostatic thrust, self-weight, and the pressure due to the pipe flow condition. When site conditions warrant, it is more economical to provide a multi-cell box culvert structure than to embark on the construction of resources cons'uming bridge structure . The hydraulic design is according to the method developed by American Association of State Highway and Transportation Officials (AASHTO Methods) and Federal Highway Administration. The structural analysis is done using computer frame analysis software developed by Department of Civil and Structures, Manchester, United Kingdom. The structural design is according to BD/37 "Design of buried concrete structures" and BS8110 "Structural Use of Concrete: Part 1 Code of Practice for Design and Construction".